Computerized alcohol screening identified more at-risk drinkers in a level 2 than a level 1 trauma center. (December 2017) - Imani, Ghasem; Barrios, Cristobal; Anderson, Craig; Hosseini Farahabadi, Maryam; Banimahd, Faried; Chakravarthy, Bharath; Hoonpongsimanont, Wirachin; McCoy, Christopher; Mercado, Georginne; Farivar, Babak; Pham, Jacqueline; Lotfipour, Shahram
Abstract Background Alcohol abuse is recognized as a significant contributor to injury. It is therefore essential that trauma centers implement screening and brief intervention (SBI) to identify patients who are problem drinkers. Although, the utility of SBI in identifying at-risk drinkers have been widely studied in level 1 trauma centers, few studies have been done in level 2 centers. This study evaluates the usefulness of SBI in identifying at-risk drinkers and to investigate the pattern of alcohol drinking among level 2 trauma patients. Methods This is a retrospective study of a convenience sample of trauma patients participating in computerized alcohol screening, brief intervention, and referral to treatment (CASI) in an academic level 1 trauma center and a nearby suburban community hospital level 2 trauma center. CASI utilized Alcohol Use Disorders Identification Test (AUDIT) to screen patients. We compared the pattern of alcohol drinking, demographic factors, and readiness-to-change scores between those screened in a level 2 and 1 trauma center. Results A total of 3, 850 and 1, 933 admitted trauma patients were screened in level 1 and 2 trauma centers respectively. There was no difference in mean age, gender, and language between the two centers. Of those screened, 10.2% of the level 1 and 14.4% of the level 2 trauma patients scored at-risk (AUDIT 8–19) (p < 0.005). Overall, 3.7% of the level 1 and 7.2% of the level 2 trauma patients had an AUDIT score consistent with dependency (AUDIT > =20) (p < 0.005). After adjusting for age, sex, education, and language, the odds of being a drinker at the level 2 center was two times of those at the level 1 center (p < 0.005). The odds of being an at-risk or dependent drinker at level 2 trauma center were 1.72 times of those at the level 1 center (p < 0.005). Conclusions Findings suggest that SBI is effective in identifying at-risk drinkers in level 2 trauma center. SBI was able to identify all drinkers, including at-risk and dependent drinkers at higher rates in level 2 versus level 1 trauma centers. Further studies to evaluate the effectiveness of SBI in altering drinking patterns among level 2 trauma patients are warranted.